Analysis of Differences in Measurement of Fair Value and Historical Value of Biological Assets on Income Smoothing (Study on Agricultural Companies in Southeast Asia And Australia) - Nopfiana Lestari; Satia Nur Maharani; M Slamet Fauzan (AIBPM Publisher, 2020)
Biological assets are assets of living things in the form of animals and plants. There have been various debates regarding the measurement of biological assets. The debate is related to the use of fair value and historical value in measuring biological assets. Historical value is considered less relevant because it does not reflect present value, while fair value is not considered as expected because it causes fluctuations in earnings and retains manipulation. This study aims to analyze the effect of fair value and historical value measurements on biological assets on income smoothing and the tendency of earnings manipulation in companies that use fair value. The results of different tests show that there is not enough evidence to state that companies that use fair value tend to have higher income smoothing than companies that use historical value. Based on the results of this study, it is suggested that investors should not only focus on company profits but also use other considerations such as future economic conditions, management performance, and government regulations.